PENANGANAN ASAP KABUT AKIBAT KEBAKARAN HUTAN DI WILAYAH PERBATASAN INDONESIA - Suryani, Anih Sri (Jurnal Aspirasi, 2012)
Forest firesthat had occurred in Indonesia often caused smoke hazewhich had a negative impact not only in Indonesia but also in neighboring countries.The negative impact of the smokehaze occurred in the health sector and the environmental, economic, and transportation sectors, as well ascross-border pollution. Strategic policies to reduce these impacts were discussed with an alytical descriptive approach. The study results showed that what has been done is still a forest fire prevention efforts, not much shaped prevention.Thus the efforts and policies were still needed, including preventive conservation efforts, strengthening legal protection  adactive participation of the local government.